Analysis of Tax Aggressiveness in Mining Companies : Study of Indonesia - Arti Ganiarti (SMART Insight, 2022)
The purpose of this study was to determine: (1) Liquidity, Profitability, and Tax Aggressiveness in Mining Companies listed on the Indonesia Stock Exchange for the period 2016-2021; (2) The Effect of Liquidity on Tax Aggressiveness in Mining Companies listed on the Indonesia Stock Exchange for the period 2016-2021; (3) The Effect of Profitability on Tax Aggressiveness in Mining Companies listed on the Indonesia Stock Exchange for the period 2016-2021. The population used is Mining Companies listed on the Indonesia Stock Exchange for the period 2016-2021. The sample obtained through purposive sampling technique was 13 companies with the total data obtained as much as 78 data. This type of research includes quantitative research with survey methods. The data analysis technique used in this research is panel data regression analysis using the Eviews 10 application program. The results of this study state that: (1) Liquidity and Profitability in Mining Companies listed on the Indonesia Stock Exchange for the period 2016-2021 tend to increase, while the CETR value tends to decrease, which means that the level of Tax Aggressiveness in Mining Companies listed on the Indonesia Stock Exchange for the period 2016-2021 is high; (2) Liquidity has a positive and significant effect on Tax Aggressiveness in Mining Companies Listed on the Indonesia Stock Exchange for the period 2016-2021; (3) Profitability has a positive and significant effect on Tax Aggressiveness in Mining Companies Listed on the Indonesia Stock Exchange for the period 2016-2021.